Evaluatıon of stress dıstrıbutıon by applıed dıfferent forces on ımmature maxıllary central teeth wıth dıfferent treatment optıons: a laboratory fınıte element stress analysıs - A Cetinkaya; LB Ayrancı (BMC Oral Health)
Abstract Background Immature maxillary central teeth can be managed by using several treatment options. The aim of this finite element stress analysis study was to evaluate the effect of different treatment procedures on the stresses on immature maxillary incisor teeth models that generated on cone beam computed tomography, by trauma and bite forces. Methods A total of 11 different models consisting of revascularization treatment using MTA and biodentine and the state of the root apex formed with cement after treatment, apexification, modified apexification, traditional root canal treatment and two different control groups have been created. 300N traumatic force and 240N bite force was applied with 90 and 130 angles. The stress values were examined in apical, middle and coronal sections using the finite element stress analysis method. Results The highest stress density was observed in the coronal root section in all models except for modified apexification treatment. While the highest vonMises stress value in coronal root dentin was found in the traditional root canal treatment group, the lowest value was found in the mature control group. In the modified apexification treatment groups, the stress was intensified in the middle and apical root section. It has been observed that in the models in which MTA is used, less stress occurs in all root parts compared to the models in which biodentine is used. Conclusions The use of MTA in immature teeth makes it more resistant to fracture compared to biodentine. Modified apexification method can reduce stress in the cervical area. More studies are needed on this subject.